PENGARUH KOAGULAN DAN KONDISI KOAGULASI TERHADAP PROFIL PROTEIN CURD KEDELAI SERTA KORELASINYA TERHADAP TEKSTUR [Effect of Coagulant and Coagulation Condition to Soybean Curd Protein Profile and Its Correlation to Texture] - Dahrul Syah; RH. Fitri Faradilla; Viktor Trisna; Yogi Karsono (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2012)
The research aims to study the effect of coagulation parameters to the electrophoretical profile of coagulated soybean protein as well as to texture properties and perception. Several coagulation parameters such as type of coagulant, concentration or age of coagulant, and coagulation temperature were studied. The type of coagulant used in this study were GDL (glucono delta Lactone) and tofu whey. The concentrations of GDL were 0.4%, 0.8%, and 1.2% and the ages of tofu whey were 1 day, 2 days, and 3 days. Two coagulation temperatures, 60°C and 80°C, were applied. The results of curd protein profile and texture profile analysis showed that coagulant type and coagulation condition did not affect the electrophoretical profile of soybean coagulated protein. However, the proportion of each subunit was affected significantly. Texture profiles, such as hardness, cohesiveness, and gumminess, were also affected by coagulant type and coagulation condition. Based on the subunits proportion, it can be concluded that 11 S and 7S protein proportions as well as the 11S/7S ratio correlated significantly with the hardness and gumminess of soybean curd made by tofu whey.